Genomic differentiation among varieties of Iberian pig - Alonso, Inés; Ibáñez-Escriche, Noelia; Noguera, José L.; Casellas, Joaquim; Martín de Hijas-Villalba, Melani; Gracia-Santana, María J.; Varona, Luis (Spanish Journal of Agricultural Research, 2020)
Aim of study: The objective of this study was to identify the autosomal genomic regions associated with genetic differentiation between three commercial strains of Iberian pig. Area of study: Extremadura (Spain). Material and methods: We used the Porcine v2 BeadChip to genotype 349 individuals from three varieties of Iberian pig (EE, Entrepelado; RR, Retinto; and TT, Torbiscal) and their crosses. After standard filtering of the Single Nucleotide Polymorphism (SNP) markers, 47, 67, and 123 haplotypic phases from EE, RR, and TT origins were identified. The allelic frequencies of 31,180 SNP markers were used to calculate the fixation index (FST) that were averaged in sliding windows of 2Mb. Main results: The results confirmed the greater genetic closeness of the EE and RR varieties, and we were able to identify several genomic regions with a divergence greater than expected. The genes present in those genomic regions were used to perform an Overrepresentation Enrichment Analysis (ORA) for the Gene Ontology (GO) terms for biological process. The ORA indicated that several groups of biological processes were overrepresented: a large group involving morphogenesis and development, and others associated with neurogenesis, cellular responses, or metabolic processes. These results were reinforced by the presence of some genes within the genomic regions that had the highest genomic differentiation. Research highlights: The genomic differentiation among varieties of the Iberian pig is heterogeneous along the genome. The genomic regions with the highest differentiation contain an overrepresentation of genes related with morphogenesis and development, neurogenesis, cellular responses and metabolic processes.